The impact of strategies for increasing vaccination coverage in children: A community clinical trial - Janaina Fonseca Almeida Souza; Thales Philipe Rodrigues da Silva; Sheila Aparecida Ferreira Latchim; Ed Wilson Rodrigues Vieira; Eunice Francisca Martins; Denisiane Geralda Araújo; Bruna de Castro da Silva; Elice Eliane Nobre Ribeiro; Fernanda Penido Matozinhos (Vaccine: X, 2024)
The Brazilian National Immunization Program (PNI) has been consolidating itself as one of the most relevant interventions in public health. Paradoxically, great challenges arise for the PNI. The phenomenon of falling vaccine coverage is observed not only in Brazil, but in several countries. In the year 2021, faced with the unfavorable scenario of a drop in vaccination coverage, the State Department of Health, and the Federal University of Minas Gerais joined forces to implement a research-intervention project. This study aimed to evaluate the impact of this intervention on vaccination coverage in children under 2 years of age and on indicators of immunization work processes. This is a community clinical trial carried out in 212 municipalities in the state. Workshops were held and Municipal Action Plans were created. Vaccination coverage data were obtained from the National Immunization Program Information System (SIPNI) and evaluated using the Mann-Whitney U Test and the McNemar Test. Work process indicators were evaluated using the Friedman and Wilcoxon tests. The results demonstrate an important improvement for most of the indicators in the three analyzed times, with statistical significance and an increase in medians and interquartile ranges. Among the indicators that showed the best performance, it is possible to mention those related to the active search by the Community Health Agent. Regarding vaccine coverage, for all immunobiologicals analyzed, there was an increase in the percentage of municipalities that reached targets when comparing the years 2022 and 2021, except for hepatitis A. The intervention research had a positive impact on vaccine coverage of children under 2 years of age and on indicators of immunization work processes in municipalities in the state of Minas Gerais, Brazil.